Responsible Beverage Service Practices: Comparison between India and Australia - Joseph, Zacharia; Thomas, Joby (Atna Journal of Tourism Studies, 2018)
Sale and consumption of alcoholic beverages have been rising globally. This is making the alcohol industry worth over $1344 billion today. This rise in alcohol consumption has not been without its gray shades in the form of alcohol abuse, alcohol-related crimes, accidents and deaths. This paper studies and compares the Responsible Beverage Service practices between India and Australia to understand its scope and impact. The study draws upon review and analysis of research and data from literature and alcohol policies of the two countries. The study reveals the similarities and differences in the approach towards Responsible Beverage Service between these two countries and suggests methods to strengthen this practice in India.